Human cytomegalovirus and neonatal infection - Shelley M. Lawrence (Current Research in Microbial Sciences)
Human cytomegalovirus is an ancient virus that has co-evolved with humans. It establishes a life-long infection in suspectable individuals for which there is no vaccination or cure. The virus can be transmitted to a developing fetus in seropositive pregnant women, and it is the leading cause of congenital infectious disease. While the majority of infected infants remain asymptomatic at birth, congenital cytomegalovirus infection can lead to substantial long-term neurodevelopmental impairments in survivors, resulting in considerable economic and social hardships. Recent discoveries regarding cytomegalovirus pathophysiology and viral replication cycles might enable the development of innovative diagnostics and therapeutics, including an effective vaccine. This Review will detail our understanding of human cytomegalovirus infection, with an in-depth discussion regarding the viral genome and transcriptome that contributes to its pathophysiology. The neonate's clinical course will also be highlighted, including maternal and neonatal testing, treatment recommendations, and long-term outcomes.